Congenital urethral fistula with a scrotal cyst in a seven-month-old male - João Baptista Ormonde; Andrea Baptista Machado; Francisco Nicanor Macedo (Elsevier, 2021)
Urethral duplication is a rare anomaly with a spectrum of anatomic types. The etiology is unknown and embriology needs to be more elucidated. It affects mainly boys and clinical presentation varies according to anatomic forms. We report an unusual Y-type urethral duplication with normal orthotopic urethra that presented with a scrotal cyst in a 7-month old boy. Our patient underwent only excision of the hypoplastic and non-functioning urethra with good functional and cosmetic result. In conclusion we suggest that on evaluating a patient with a scrotal cyst a Y-type urethral duplication should be suspected and a radiographic study must be done to recognize the normal urethra and choose the best surgical treatment.